Analisi Efisiensi Teknis, Alokatif dan Ekonomi Produksi Kubis di Kabupaten Karo - Esra Frandika Barus; Dominicus Savio Priyarsono; Sri Hartoyo (JURNAL AGRICA, 2021)
The productivity level of cabbage farming in North Sumatra Province is low compared to other provinces on the island of Sumatra, where Karo Regency represents the general condition in North Sumatra Province. This study aims to estimate the level of technical, allocative, economic efficiency and the factors that affect the technical inefficiency of cabbage farming. The production function uses the Cobb-Douglas production function. Data analysis used the stochastic frontier method with a total sample of 116 farmers. The results of the analysis showed that cabbage farming in Karo District had not achieved technical, allocative and economic efficiency. The average technical, allocative and economic efficiency values of the respondent farmers were 0,697, 0,374 and 0,215. These results indicate that low efficiency is a contributing factor to the low productivity of farmer respondents' cabbage in Karo District. Factors that have a significant effect on efficiency are farming experience, labor ratio, land ownership status and cabbage harvest age. Based on the estimation results, the research policy suggestions include; increase farmer activeness to be involved in farmer groups, build and facilitate the growth and development of agricultural institutions and provide good seeding training so that farmers have good skills, thus improving the technical efficiency of cabbage farming in Karo District.